(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To determine correlations of the parameters of the oxidative-anti-oxidative system in the lens, aqueous humor and tear fluid with the grade of lens opacity in rabbits with cataract and/or bacterial keratitis treated versus not treated with methyl-ethyl pyridinol hydrochloride (MH). Methods: Fifty-four adult Chinchilla rabbits were used for all experiments. Superficial bacterial keratitis only was induced only in the right eye (groups 1 and 2), and each of animals in group 2 received five four-week cycles of four-times-a-day-treatment with MH in the right eye separated by four-week breaks. In animals of groups 3 and 4, cataract was induced by nine-hours-a-day total exposure to 350-1150 nm ultraviolet (UV) radiation from a mercury-arc lamp for a period 40 weeks. Each of animals in group 4 received MH treatment in both eyes using the same scheme as noted above. In animals of groups 5 and 6, cataract was induced in the same way as in animals of group 3, and keratitis was induced in the same way as in animals of group 1. Each of animals in group 6 received MH treatment in the right eye using the same scheme as noted above. Group 7 comprised intact control rabbits. The Spearmen rank correlation was used to assess associations between the grade of lens opacity, activities of glutathione peroxidase (GP) and catalase (CT), and levels of malondialdehyde (MDA) and diene conjugate (DC). Results: The grade of lens opacity was negatively correlated with the activities of GP and CT, and positively correlated with the levels of lipid peroxidation products (MDA and DC) for rabbits with keratitis only, cataract only, and especially keratitis plus cataract, treated or not treated with MH. There was no substantial change in the values of correlation coefficients for rabbits treated with MH compared to those not treated with MH. Conclusion: Our findings of correlations between the above-mentioned parameters indicate the important role the metabolic abnormalities have in the formation of structural and functional changes in the lens of animals with corneal inflammation. These findings also lay ground for introducing pathogenesis-targeted metabolic correction with MH for oxidative-antioxidative system imbalance in ocular tissues